Why is the Groundwater Level Rising? A Case Study Using HARTT to Simulate Groundwater Level Dynamic: Yihdego et al. (1st December 2017) - Yihdego, Yohannes; Danis, Cara; Paffard, Andrew
ABSTRACT: : Groundwater from a shallow unconfined aquifer at a site in coastal New South Wales has been causing recent water logging issues. A trend of rising groundwater level has been anecdotally observed over the last 10 years. It was not clear whether the changes in groundwater levels were solely natural variations within the groundwater system or whether human interference was driving the level up. Time series topographic images revealed significant surrounding land use changes and human modification to the environment of the groundwater catchment. A statistical model utilising HARTT (multiple linear regression hydrograph analysis method) simulated the groundwater level dynamics at five key monitoring locations and successfully showed a trend of rising groundwater level. Utilising hydrogeological input from field investigations, the model successfully simulated the rise in the water table over time to the present day levels, whilst taking into consideration rainfall and land changes. The underlying geological/land conditions were found to be just as significant as the impact of climate variation. The correlation coefficient for the monitoring bores (MB), excluding MB4, show that the groundwater level fluctuation can be explained by the climate variable (rainfall) with the lag time between the atypical rainfall and groundwater level ranging from 4 to 7 months. The low R 2 value for MB4 indicates that there are factors missing in the model which are primarily related to human interference. The elevated groundwater levels in the affected area are the result of long term cumulative land use changes, instigated by humans, which have directly resulted in detrimental changes to the groundwater aquifer properties.